Mycobacterium bovis BCG as immunostimulating agent prevents the severe form of chronic experimental Chagas disease - Arce-Fonseca, Minerva; Mata-Espinosa, Dulce; Aranda-Fraustro, Alberto; Rosales-Encina, José Luis; Flores-Valdez, Mario Alberto; Rodríguez-Morales, Olivia (Frontiers in Immunology, 2024)
Currently there is no vaccine against Chagas disease (ChD), and the medications available confer multiple side effects. Mycobacterium bovis Bacillus Calmette-Guérin (BCG) produced balanced Th1, Th2 and Th17 modulatory immune responses, and has improved efficacy in controlling chronic infections through nonspecific immunity. We aimed to improve the response to infection by inducing a stronger immune response and greater protection against the parasite by trained immunity. BALB/c mice were immunized with BCG subcutaneously, and 60 days later, they were infected with Trypanosoma cruzi intraperitoneally. The evaluation of the progression of the disease from the acute to the chronic stage, analyzing various aspects such as parasitemia, survival, clinical status, humoral and cellular immune response, as well as the appearance of visceral megas and the histopathological description of target organs were performed. Vaccination reduced parasitemia by 70%, and achieved 100% survival in the acute stage; although the presentation of clinical signs was reduced, there was no increase in the antibody titer or in the differential production of the isotypes. Serum cytokines production indicated a proinflammatory response in infected animals; while in those who received BCG, the response was balanced by inducing Th1/Th2 type cytokines, with a better prognosis of the disease in the chronic stage.